Human papillomavirus genotype-specific risks for cervical intraepithelial lesions. Issue 4 (3rd April 2021) - Nygård, Mari; Hansen, Bo T.; Kjaer, Susanne K.; Hortlund, Maria; Tryggvadóttir, Laufey; Munk, Christian; Lagheden, Camilla; Sigurdardottir, Lara G.; Campbell, Suzanne; Liaw, Kai-Li; Dillner, Joakim
ABSTRACT: Prevalence of different HPV genotypes is changing after HPV vaccination. The associated risks are needed for optimizing cervical cancer screening. To estimate HPV type-specific prevalence, odds ratio (OR), and positive predictive value (PPV) for cervical cytological abnormalities, we determined 41 different HPV genotypes in cervical samples from a population-based sample of 8351 women aged 18–51 years before HPV vaccination era (V501-033; NCT01077856). Prevalence of HPV16 was 4.9% (95% CI: 4.4–5.5) with the PPV for high-grade cytology 11.2%, and OR 11.9 (95% CI: 8.5–16.5). Carcinogenic HPVs included in the nonavalent vaccine (HPV16, 18, 31, 33, 45, 52, 58) had a population prevalence of 14.4% (95% CI: 13.5–15.4), with PPV of 8.0% (95% CI: 6.8–9.3) and OR 23.7 (95% CI: 16.0–63.5) for high-grade cytology. HPV types currently included in most screening tests, but not vaccinated against (HPV35, 39, 51, 56, 59, 66, 68) had a joint prevalence of 8.5% (95% CI: 7.8–9.2) with PPV of 4.4% (95% CI: 3.3–5.7) and OR of 2.9 (95% CI: 2.0–4.0) for high-grade cytology. The other 27 non-carcinogenic genotypes had a prevalence of 11.8%, PPV of 2.9% (95% CI:2.1–3.9), and OR 1.5 (95% CI: 1.1–2.2.) for high-grade cytology. These results suggest that HPV screening tests in the post-vaccination era might perform better if restricted to the HPV types in the nonavalent vaccine and screening for all 14 HPV types might result in suboptimal balance of harms and benefits.